Piezoelectric and dielectric properties of (Bi0.5Na 0.5)TiO3-Ba(Ti0.95Zr0.05)O 3 system - Sawangwan N. (2014)
The morphotropic phase boundary of bismuth sodium titanate (BNT) and barium zirconate titanate (BZT) ceramics were study. In the case of (1-x)BNT-xBZT where x = 0.06 to 0.12 mol. The solid solution ceramics which have the combine phases between rhombohedral and tetragonal are obtained at x = 0.06 to 0.11 mol. The maximum of piezoelectric and dielectric constants are obtained for 0.93BNT-0.07BZT ceramics at 161 pC/N and 1839, respectively. This may be indicated that this composition is nearly existed of MPB region.